2008
DOI: 10.1088/0964-1726/17/2/025020
|View full text |Cite
|
Sign up to set email alerts
|

Self-repairing performance of concrete beams strengthened using superelastic SMA wires in combination with adhesives released from hollow fibers

Abstract: By taking advantage of the superelastic effect of shape memory alloy (SMA) and the cohering characteristic of repairing adhesive, a smart self-repairing concrete beam with damage self-repairing performance has been developed. In order to verify the potential self-repairing capacity of smart concrete beams reinforced with SMA wires and brittle fibers containing adhesives, static loading tests were conducted. Experimental results show that the superelastic SMA wires added self-restoration capacity to concrete be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 12 publications
1
36
0
Order By: Relevance
“…Therefore, Kuang and Ou [42,43] combined this approach with a mechanism to reduce the crack width. They included both SMA wires and continuous adhesive filled glass tubes.…”
Section: Approaches To Self-healingmentioning
confidence: 99%
“…Therefore, Kuang and Ou [42,43] combined this approach with a mechanism to reduce the crack width. They included both SMA wires and continuous adhesive filled glass tubes.…”
Section: Approaches To Self-healingmentioning
confidence: 99%
“…Kuang and Ou and Li et al found that the SMA wire as reinforcing bar can make cracks close and perform the task of emergency damage repair in concrete structures. The cracks are closed due to the super elastic behavior of embedded SMAs (as shown in Figure 26) (Kuang and Ou, 2008;Li et al, 2006a). Schlangen and Sangadji developed self-healing asphalt concrete by embedding tiny steel fibers and using induction energy.…”
Section: Autonomous Self-healing Concrete and Structuresmentioning
confidence: 99%
“…The study showed the bending behaviour of a superelastic bar in reversed cyclic loadings and the estimation of the stiffness and damping ratio. Researchers have also used the superelastic property of SMAs for selfrepairing of concrete beams (Kuang and Ou, 2008). For RC columns, superelastic SMA bars replaced steel reinforcements in the plastic hinge region to reduce the residual displacement in RC columns (Saiidi and Wang, 2006).…”
Section: Introductionmentioning
confidence: 99%